2017
DOI: 10.1002/ejic.201700083
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Synthesis of Boron‐ and Germanium‐Substituted Unsymmetrical Disilazanes

Abstract: We recently reported on the successful use of the Karstedt catalyst for the synthesis of organofunctionalized disilazanes, and the aim of this work was to check the activity of this catalyst in the preparation of novel unsymmetrical boronand germanium-functionalized disilazanes. High selectivity, rel- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Hydrosilylation of unsaturated organoborane compounds bearing functional groups such as vinyl, allyl and acetylene has been reported in many publications [34–36] . In our previous research, we studied the reactions of obtaining silsesquioxane derivatives from unsaturated boranes in a form of vinyl‐ and allylboronates by hydrosilylation with Si−H moiety‐bearing mono‐ and octaspherosilicates catalyzed by Karstedt's catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrosilylation of unsaturated organoborane compounds bearing functional groups such as vinyl, allyl and acetylene has been reported in many publications [34–36] . In our previous research, we studied the reactions of obtaining silsesquioxane derivatives from unsaturated boranes in a form of vinyl‐ and allylboronates by hydrosilylation with Si−H moiety‐bearing mono‐ and octaspherosilicates catalyzed by Karstedt's catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Hydrosilylation of unsaturated organoborane compounds bearing functional groups such as vinyl, allyl and acetylene has been reported in many publications. [34][35][36] In our previous research, we studied the reactions of obtaining silsesquioxane derivatives from unsaturated boranes in a form of vinyl-and allylboronates by hydrosilylation with SiÀ H moiety-bearing mono-and octaspherosilicates catalyzed by Karstedt's catalyst. High conversion of substrates prompted us to obtain new borasilsesquioxane derivatives in a hydrosilylation reaction with commercially available compounds containing SiÀ H groups by a reverse approach.…”
Section: Introductionmentioning
confidence: 99%
“…[15] A large number of studies have shown that the ultimate properties of ceramic materials are closely related to the elemental components that they contain. [16,17] For example, the SiC binary ceramic system exhibits β-SiC crystallization at 1000 °C, and when it reaches 1200 °C, the material can no longer maintain its ceramic properties. [18,19] When N is introduced to form a ternary ceramic system, the crystallization temperature can rise to 1400 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, conventional methods using halo‐compounds are used to modify their structure, however catalytic solutions are becoming increasingly investigated . On the other hand, the boron modification of various compounds, polymers, and nanoparticles is attractive for a wide range of applications . Si‐ O ‐B moiety, which is a core of poly(borasiloxane)s, is very interesting in terms of modern polymer chemistry .…”
Section: Introductionmentioning
confidence: 99%